TEOLOGI ISLAM KONTEMPORER CORAK PEMIKIRAN HARUN NASUTION DAN HM RASJIDI - Masruri, Ahmad (Institut PTIQ Jakarta, 2023)
The aim of this research is to discuss the contemporary kalam thinking of two figures in Indonesian Islamic philosophy, Harun Nasution and HM. Rasjidi. In the history of Islamic thought, both of them are very well known among figures of Indonesian Islamic thought. This research uses qualitative research with data collection techniques, namely literature (library research) related to the theology of contemporary thought figures. The results of the research show that Harun Nasution's thinking in the concept of freedom and God's absolute will is more similar to the understanding of the Muktazilah theological school. Regarding God's justice, Harun Nasution compares and explains several schools of Islamic theology without taking sides. In understanding destiny and sunatullah, Harun emphasized the use of reason because this will influence the productive nature of the people which will have an impact on the development and progress of the Muslim community. In Harun's view, mysticism or Sufism is considered neo-Sufism. Meanwhile, HM Rasjidi is of the view that kalam science is not the same as theology. Rasyidi's view of faith is that it does not just unite humans with God, but can also be seen from the consequential dimension or human-human relationship, namely life in society